Electrical cortical stimulations modulate spike and post-spike slow-related high-frequency activities in human epileptic foci. Issue 8 (August 2020) - Nakatani, Mitsuyoshi; Matsumoto, Riki; Kobayashi, Katsuya; Hitomi, Takefumi; Inouchi, Morito; Matsuhashi, Masao; Kinoshita, Masako; Kikuchi, Takayuki; Yoshida, Kazumichi; Kunieda, Takeharu; Miyamoto, Susumu; Takahashi, Ryosuke; et al.
Highlights: The number and amplitude of spikes decreased after 50-Hz stimulation of the seizure onset zone (SOZ). Spike-related high-frequency activities (HFAs) also decreased and post-spike slow wave-related HFAs increased. 50-Hz stimulation of the SOZ modulated cortical excitability toward less excitation and more inhibition. Abstract: Objective: Using interictal epileptiform discharges (IEDs), consisting of spikes and post-spike slow waves (PSSs), and IED-related high-frequency activities (HFAs), we elucidated inhibitory effects of electrical cortical stimulation (ECS) on human epileptic foci. Methods: We recruited 8 patients with intractable focal epilepsy, and 50-Hz ECS was applied to the seizure-onset zone (SOZ) and non-SOZ. Before (5-min) and after (20-min) ECS, we evaluated the number of IED, the amplitudes of spikes and PSSs, spike-related HFA power, and PSS-related low gamma (30–50 Hz) activities. Results: SOZ stimulation significantly decreased the number of IEDs and amplitude of spikes. Spike-related HFA power values in fast ripple (200–300 Hz) and ripple (80–150 Hz) bands were significantly suppressed only by SOZ stimulation in 4 and 3 patients, respectively. Among 4 patients with discrete PSSs, the amplitude ratio of spike/PSS decreased and the PSS-related low gamma activity power increased significantly in 2 patients and marginally in 1 patient. Conclusions: ECS potentially modulates cortical excitability by reducing excitation and increasing inhibition, and monitoring IED-related HFAs may help achieve the optimal effects of ECS. Significance: IED and IED-related HFAs are dynamic, potential surrogate markers for epileptic excitability during the interictal period.